Childhood injury surveillance in a Nigerian teaching hospital. (7th October 2012) - Ofoegbu, C; Nasir, A; Burrows, S; Abdur-Rahman, L; Babalola, O; Yusuf, A; Solagberu, B
Abstract : Background: Information on childhood injury in Nigeria is scanty. There is a need to establish and strengthen childhood injury monitoring and reporting as a useful tool for childhood injury control. Aims/Objectives/Purpose: The aim of this pilot study was to develop a childhood injury surveillance system at University of Ilorin Teaching Hospital, Nigeria. Methods: All children aged ≤15 years presenting with injuries at the emergency room (ER) during a 10-month period were included. A structured form was designed to obtain information on injury history from parents/guardians. Clinical details were extracted from medical records. Data were compared using χ 2 /Fisher's exact test as appropriate. Results/Outcome: A total of 111 children presented to the ER with injuries (10% of all patients seen). The median age was 72 months, with a male : female ratio of 1.9 : 1. Leading mechanisms of unintentional injuries were road traffic crashes (RTC) (44%), falls (37%) and burns (13%). In 58% of RTCs, the injured child was a pedestrian. Injuries mostly occurred in homes (43%) and on streets/highways (39%). Major injuries involved the head and neck (42%) and extremities (27%). Most injuries were moderate to severe (76%) with 12% resulting in death. RTCs accounted for 46% mortality. Mortality was significantly influenced by age (p=0.028), nature of injury (p=0.013) and injury severity (p=0.000). Significance /Contribution to the Field: The injury surveillance system provided valuable information on childhood injuries presenting to the ER. The results suggest that improved home and road safety and increased parental supervision are needed to reduce childhood injury.